Phylogeny, Resistome, and Virulome of Escherichia coli Causing Biliary Tract Infections - Rodríguez-Villodres, Ángel (J Clin Med, 2019)
Escherichia coli is the most frequent Gram-negative bacilli involved in intra-abdominal infections. However, despite high mortality rates associated with biliary tract infections due to E. coli, there is no study focusing on this pathogen. In this study, we have characterized a group of 15 E. coli isolates obtained from 12 patients with biliary tract infections. Demographic and clinical data of the patients were recovered. Phylogeny, resistome, and virulome analysis through whole genome sequencing and biofilm formation were investigated. Among the 15 E. coli isolates, no predominant sequence type (ST) was identified, although 3 of them belonged to unknown STs (20%). Resistance to ampicillin, amoxicillin/clavulanic acid, cotrimoxazole, and quinolones was more present in these isolates; whereas, third and fourth generation cephalosporins, carbapenems, amikacin, tigecycline, and colistin were highly active. Moreover, high diversity of virulence factors has been found, with sfa, fimH, and gad the most frequently detected genes. Interestingly, 26.6% of the E. coli isolates were high biofilm-producers. Altogether, our data characterized for the first time E. coli isolates associated with biliary tract infections in terms of genomic relationship, resistome, and virulome.